2021
DOI: 10.3390/microorganisms9122524
|View full text |Cite
|
Sign up to set email alerts
|

Succession Analysis of Gut Microbiota Structure of Participants from Long-Lived Families in Hechi, Guangxi, China

Abstract: The gut microbiota structure has been proposed to be involved in longevity. In this study, trajectories of age-related changes in gut microbiota were analyzed by comparing the gut microbiota composition from long-lived families. A specific bacterial community pattern and signature taxa of long-lived people were found in long-lived families, such as the enrichment of Enterobacteriaceae in all age groups and the higher abundances of Christensenellaceae, Verrucomicrobiaceae, Porphyromonadaceae, Rikenellaceae, Mog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 36 publications
6
23
0
Order By: Relevance
“…The methods used for fecal microbial genomic DNA extraction, library construction, sequencing, and bioinformatics analysis were the same as we previously described [ 5 ]. The analysis of α-diversity, which included the calculation of observed OTU numbers, Chao1, Shannon index, and Simpson index in all samples, was estimated by MOTHUR (v1.31.2) at the OTU level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used for fecal microbial genomic DNA extraction, library construction, sequencing, and bioinformatics analysis were the same as we previously described [ 5 ]. The analysis of α-diversity, which included the calculation of observed OTU numbers, Chao1, Shannon index, and Simpson index in all samples, was estimated by MOTHUR (v1.31.2) at the OTU level.…”
Section: Methodsmentioning
confidence: 99%
“…Aging is associated with changes in the gut microbiota that might result in dysbiosis and illnesses [ 4 ]. It is reported that specific beneficial bacteria, such as Bifidobacterium, are depleted in elderly individuals [ 4 ], and the abundance of Lactobacillus in the elderly from a long-lived village was higher than in controls [ 5 ]. Therefore, regulating the gut microbiota may provide an opportunity to improve health among the elderly [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of Akkermansia are also found in healthy individuals' feces than in feces from individuals with inflammatory or metabolic diseases (70). The families to which ASVs associated with RSB are assigned, Verrucomicrobiaceae, Rikenellaceae, Ruminococcaceae, Lachnospiraceae, Christensenellaceae, and Mogibacteriaceae, were also enriched in long-lived families in a recent study (71). Additionally, the family Christensenellaceae consistently has been associated with reduced visceral fat mass and leanness (72), and Christenellaceae, Mogibacteriaceae, and Rikenellaceae were associated with leanness, longevity, healthy aging, and protective of cardiovascular and metabolic disorders (73,74).…”
Section: Discussionmentioning
confidence: 95%
“…Administration of R. intestinalis increased the levels of certain beneficial gut bacteria. Porphyromonadaceae abundance increased in long-lived populations, and the proportion of R. intestinalis also increased ( Ren et al, 2021 ). The abundance of Barnesiella , Porphyromonadaceae , and Roseburia also increased after vitamin D1 administration in patients with Crohn’s disease ( Schäffler et al, 2018 ), indicating that these bacteria may function synergistically.…”
Section: Discussionmentioning
confidence: 99%